On Some Complete Monotonicity of Functions Related to Generalized k−Gamma Function - Hesham Moustafa; Hanan Almuashi; Mansour Mahmoud (Journal of Mathematics)
In this paper, we presented two completely monotonic functions involving the generalized k−gamma function Γkx and its logarithmic derivative ψkx, and established some upper and lower bounds for Γkx in terms of ψkx.